Research on the Application of Agricultural Engineering Technology in Agricultural Modernization. (November 2020) - Zhang, Heyi
Abstract: In recent years, with the rapid improvement of China's science and technology level, China's agricultural engineering technology has also made considerable progress. The development of agricultural engineering technology provides an important technical foundation for the realization of agricultural modernization, especially in the effective use of agricultural resources, the improvement of agricultural labor productivity, and the transformation of agricultural production and operation methods. Therefore, we must increase the promotion and application of agricultural engineering technology in various agricultural production and operation activities. This will help promote the gradual development of China's agricultural production in the direction of mechanization, automation, informationization and intelligence, so as to fully realize the modernization of China's agriculture.